Commutators of Lipschitz Functions and Singular Integrals with Non-Smooth Kernels on Euclidean Spaces (Analysis in Theory and Applications, 2016)
In this article, we obtain the $L^p$-boundedness of commutators of Lipschitz functions and singular integrals with non-smooth kernels on Euclidean spaces.
Keywords: Commutators; singular integrals; maximal functions; sharp maximal functions; muckenhoupt weights; Lipschitz spaces.